2011
DOI: 10.1590/s0102-77862011000200003
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade sazonal da condutância estomática em um ecossistema de manguezal amazônico e suas relações com variáveis meteorológicas

Abstract: RESUMONo presente trabalho foram estudadas as variações da condutância estomática (g s ) para o período chuvoso (março) e seco (agosto) do ano de 2003, e suas relações de dependência com algumas variáveis meteorológicas medidas em um ecossistema de manguezal amazônico. As informações utilizadas foram do projeto ECOBIOMA, parte integrante do Experimento de Grande Escala da Biosfera-Atmosfera da Amazônia (LBA). A g s acompanha a tendência de variação do balanço de radiação, atingindo valores máximos durante o di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 14 publications
1
8
0
9
Order By: Relevance
“…Silva et al (2010) The PI 189 accession had the lowest mean value for net CO 2 assimilation and stomatal conductance ( Figures 1 and 2). These results are correlated, since stomatal conductance is directly related to the net rate of CO 2 assimilation, as low values may be associated with partial stomatal closure, reducing CO 2 entry to the rubisco carboxylation sites, thereby reducing net photosynthesis (DALLAGNOL et al, 2011;RODRIGUES, et al, 2011). Similar values for stomatal conductance of around 0.316 to 0.420 mol m -2 s -1 were reported by Silva et al (2010) The accessions showed no significant difference for internal CO 2 concentration (Figure 3).…”
Section: Resultssupporting
confidence: 59%
“…Silva et al (2010) The PI 189 accession had the lowest mean value for net CO 2 assimilation and stomatal conductance ( Figures 1 and 2). These results are correlated, since stomatal conductance is directly related to the net rate of CO 2 assimilation, as low values may be associated with partial stomatal closure, reducing CO 2 entry to the rubisco carboxylation sites, thereby reducing net photosynthesis (DALLAGNOL et al, 2011;RODRIGUES, et al, 2011). Similar values for stomatal conductance of around 0.316 to 0.420 mol m -2 s -1 were reported by Silva et al (2010) The accessions showed no significant difference for internal CO 2 concentration (Figure 3).…”
Section: Resultssupporting
confidence: 59%
“…The VPD was calculated from the Tetens equation (Rodrigues et al, 2011;Vianello & Alves, 2012), which is obtained by the difference between saturation vapor pressure (e s ) and actual vapor pressure (e). To calculate the e s it was taken into consideration the air temperature value, according to the Eq.…”
Section: Methodsmentioning
confidence: 99%
“…The saturation vapor pressure depends on air temperature and as it increases, higher is the saturation vapor pressure. The actual vapor pressure depends on air relative humidity along with the saturation vapor pressure, and it increases increasing the relative humidity (Rodrigues et al, 2011;Vianello & Alves, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The vapor pressure deficit (VPD) was obtained from the Equation 1: The saturated vapor pressure (e s ) was calculated using the psychrometric chart available at http://physics.holsoft.nl/physics/ ocmain.htm. The partial vapor pressure (e a ) was obtained according to Rodrigues et al (2011) …”
Section: Methodsmentioning
confidence: 99%